(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Research has been conducted on handball. This has been done by applying the Marzano model to a handball lesson in a practical and cognitive manner. This is so that the overall characteristics of educational theories can be applied. From this, the model derives its dimensions, which is considered one of the innovations in the educational arena through what many educators do. This model can be used as a frame of reference and the objectives that academic content seeks to achieve. The model of learning consists of five facets and considers the first two facets (positive attitudes toward learning) and the fifth facets (productive habits of the mind) as the base or medium for learning. This is done through the ability to perform and memorize the skill and link what the learner acquires to previous experience. University is also one of the most crucial stages in a learner’s life. This is because of its crucial role in preparing him to learn theories to continue his education. It also prepares him for practical life and reveals his preparations. The research problem is identified in the educational methods used in teaching this subject, as well as the method of explanation and clarification on the educational side of the main section, to ensure that the explanation is not repeated and the information is returned to the learner again on the applied side of the main section, and to take advantage of the time in performing the skills with more repetitions, so that these times or periods are prolonged. This causes the learners to become tired and bored, which does not result in the anticipated benefit from the applied side of the learning process. Therefore, the researcher resorted to educational alternatives using the Marzano model. This may have a positive impact on learning handball players’ shooting skills. The researcher used the experimental method by designing two equal groups (experimental and control) with pre and post-tests. The research community was determined by the second-year students of the College of Physical Education and Sports Sciences - University of Babylon for the academic year (2022-2023), whose number is (122) students. The sample of the main experiment included (40) students and was divided into two groups (control and experimental) with (20) students for each group, and the statistical package (SPSS) was used for data processing.